FAIR VALUE ACCOUNTING DAN KEMAMPUAN LABA MEMPREDIKSI LABA DAN ARUS KAS MASA DEPAN MENGGUNAKAN PENDEKATAN BALANCE SHEET DAN INCOME STATEMENT - Sitohang, Pardamean; Nikmah, Nikmah (UNIB Press, 2015)
This study aims to determine whether the disclosure of the fair value of financial instruments used in the financial statements may improve the ability of earnings to predict future earnings and future cash flows after the application of PSAK 50 and 55 (revised 2006). Fair value measurements using two approaches, namely the balance sheet approach and an income statement approach. This study used a banking company listed on the BEI in the period 2010-2013. Using purposive sampling method, the balance sheet approach used a sample of 28 companies and approach to the income statement using a sample of 19 companies. Data analysis methods used in this study are Moderated Regression Analysis (MRA) and multiple regression analysis using SPSS 16. The results of this study showed that after the application of PSAK 50 and 55 (revised 2006) can improve the relevance of information on the fair value of financial instruments. This is supported by the results of studies showing that the fair value of financial instruments can improve the ability of earnings to predict future earnings and future cash flows using the balance sheet approach. However, this research has not been able to provide evidence that the components of other comprehensive income can provide an incremental effect on the ability of earnings to predict future earnings and future cash flows using an income statement approach.